Marine seismic surveys - A study of environmental implications - McCauley, Robert; Fewtrell, Jane; Duncan, Alec; Jenner, Curt; Jenner, Micheline-Nicole; Penrose, John; Prince, Robert; Adhitya, Anita; Murdoch, Julie; McKabe, Kathyrn (Australian Petroleum Production and Exploration Association, 2000)
© CSIRO 2000.